Neonatal Orbital Abscess after Sinus Surgery: Case Report and Brief Review. (22nd July 2013) - Yang, Elizabeth; Fisher, Mark; Levin, Flora; Servat, Juan
ABSTRACT: Orbital abscess formation in neonates is rare, with only 12 cases reported in the literature. We present a case of orbital cellulitis with orbital abscesses following repair of congenital choanal atresia in a 2-week-old neonate. This is the first reported case of an orbital abscess following a sinus procedure in a neonate.